2021
DOI: 10.1097/ccm.0000000000005088
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Circulating Immune Cells Profiles and Kinetics Between Coronavirus Disease 2019 and Bacterial Sepsis*

Abstract: OBJECTIVES: Although clinical presentation of coronavirus disease 2019 has been extensively described, immune response to severe acute respiratory syndrome coronavirus 2 remains yet not fully understood. Similarities with bacterial sepsis were observed; however, few studies specifically addressed differences of immune response between both conditions. Here, we report a longitudinal analysis of the immune response in coronavirus disease 2019 patients, its correlation with outcome, and comparison bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…The quick spread of Coronavirus disease (COVID-19) resulted in a pandemic in the whole world, reaching more than 100 million cases and 2 million deaths due to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [1]. The progression, severity, and mortality of COVID-19 differ from no, mild, or moderate symptoms in most of the patients, while up to 15% develop the severe and critical form of the disease with high mortality rates [2].…”
Section: Introductionmentioning
confidence: 99%
“…The quick spread of Coronavirus disease (COVID-19) resulted in a pandemic in the whole world, reaching more than 100 million cases and 2 million deaths due to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [1]. The progression, severity, and mortality of COVID-19 differ from no, mild, or moderate symptoms in most of the patients, while up to 15% develop the severe and critical form of the disease with high mortality rates [2].…”
Section: Introductionmentioning
confidence: 99%
“…Intervention strategies, such as anti-programmed cell death (PD)-1/PD-L1 mAb, blocking cytotoxic T lymphocyte antigen (CTLA)-4, and blocking 2B4, have improved survival in experimental models of sepsis and recent clinical trials through improved T cell-induced immunosuppression (46,(55)(56)(57)(58). The degree of sepsis-induced inflammation, including the level of immunosuppression, is defined by specific host factors (such as age, gender, alcoholism, repeated nosocomial infection, frequency in hospital, chronic comorbidities, immunosuppressant use, malignant tumor, site of infection, splenectomy, trauma, and stress state) (59-66), pathogen status (such as multiple drugresistant organisms, malaria, SARS-CoV-2) (7,26,67,68), and the duration of sepsis (6,28,35,44,46,61,69,70).…”
Section: Sepsismentioning
confidence: 99%
“…In addition, multiple clinical studies show that amplification of CD4+CD25+ Tregs and increased Foxp3 levels may increase risks of nosocomial infections or secondary infections in sepsis (61,68,147). Using a "two-hit" CLP model with intratracheal injection of Pseudomonas aeruginosa, which mimics clinical conditions of secondary infection, Hu et al demonstrated that the absolute number of Foxp3+ Tregs in both spleen and lungs increased 24 hours after secondary P. aeruginosa infection.…”
Section: Host-dependent Treg Patterns In Sepsismentioning
confidence: 99%
“…The systemic immune-inflammation/cytokine storm, which constitutes an exaggerated host immune response associated with excessive production of pro-inflammatory cytokines, chemokines and acute phase proteins, is a hallmark feature in the acute phase of sepsis (18,(64)(65)(66)(67)(68)(69)(70)(71). This is one of the main causes of death and ICU acquired complications, including SIRS and compensatory anti-inflammatory response syndrome (CARS), and is defined by the host status (57,(72)(73)(74)(75)(76), pathogens (77,78) and the time span of sepsis (71,(79)(80)(81)(82)(83)(84). T regs have been shown to have a role on the inhibition of sepsis-induced amplifying systemic immuno-inflammation/cytokine storm and on the protection of organs in the early stage of sepsis (53,85,86).…”
Section: Suppression Of Sepsis-induced Systemic Immune-inflammation/c...mentioning
confidence: 99%